A baseline study to evaluate the groundwater conditions and predict future impacts of mining at Matsopa minerals - Mokitlane, Lerato (University of the Free State, 2018)
This dissertation investigates the possible contamination of the groundwater environment as result of the mining of a bentonite body at Matsopa Minerals. The study is crucial because the community in the area solely depends on groundwater for domestic use as well as livestock watering. A number of investigations were carried out, namely: 1) a hydrocensus to investigate the water use, groundwater flow direction, number of boreholes in use and surface water points, 2) geophysical investigations to investigate the presence of geological structures that act as groundwater conduits, 3) geochemical investigations of the ore and host rock to determine the character potential contaminant impacts, 4) groundwater monitoring to determine whether mining has impacted on the groundwater quality, and 5) aquifer hydraulic testing to determine the hydraulic parameters of the aquifer system. The results obtained from the hydrocensus show that the groundwater is used for domestic use, livestock watering and irrigation, on a number of farms surrounding the mine. From the electrical conductivity (EC) profiling done on two boreholes, one borehole was determined to be sited on a fractured aquifer system. The geophysical investigations were conducted using two methods, namely: the magnetic and electrical resistivity tomography (ERT) methods. Both methods revealed the presence of dolerite structures adjacent to and in the vicinity of the mine and the opencast pit. These structures are likely to be associated with fractures, joints, cracks and fissures which form preferential pathways for groundwater transmission. Geochemical investigations were carried out by using X-ray fluorescence (XRF) and X-ray diffraction (XRD). The methods showed that both the ore and host are dominated by SiO2. The trace elements that could pose a threat to the environment or human health occur at low concentrations. Groundwater monitoring was conducted on a bimestrial basis. The groundwater was found to be with little or no evidence of contaminant impacts from mining. Elevated nitrate concentrations were found in the hydrochemistry analysis from the surrounding farms as result of agricultural activities. During the monitoring events groundwater levels were recorded in the boreholes of the surrounding farms, there was increasing levels in the groundwater. This showed that recharge of the groundwater system was taking place as result of higher rainfall experienced as compared to the preceding years. A hydraulic test was conducted on the aquifer system by performing a pump test to obtain aquifer parameters and flow characteristics. Transmissivity (T) measurements were obtained from recovery data and the flow regime determined was the acting radial flow regime. The storativity could not be calculated because the pump test was conducted on single well with no observation boreholes. The T-value obtained showed that the aquifer is a good groundwater transmissive aquifer. The results of the studies have indicated there has not been significant detrimental impact on the groundwater environment as result of the bentonite mining at Matsopa Minerals. The groundwater contamination found in the area is the result of agricultural activities with high nitrate concentrations above the regulated standard limits. The nitrate can be treated by using any of these processes: reverse osmosis and biological denitrification.
Dissertation (M.Sc. (Institute for Groundwater Studies)--University of the Free State, 2018
Keywords: Mines and mineral resources; Mining geology; Groundwater